Oral Health Knowledge, Attitudes and Behaviors in Dental and Oral Health Program Students: A Descriptive Cross-Sectional Study - Zeynep Taştan Eroğlu; Tuğçe Yıldız (European Annals of Dental Sciences)

(untitled)
Purpose: The objective of this study was to assess the oral health attitudes, knowledge, and behaviors of students in dental and oral and dental health programs before and after periodontology clinical training, and to investigate the correlations between these variables and sociodemographic factors.Materials and Method: In this study conducted at the end of the spring semester in 2022, we utilized the Turkish version of the Hiroshima University Dental Behavioral Inventory (HU-DBI). Sociodemographic data, oral hygiene practices, and smoking habits were collected through a questionnaire. Higher HU-DBI scores reflect improved oral health attitudes and behaviors. The data were statistically analyzed with a significance level set at p<0.05.Results: This study involved 295 students: 151 preclinical dental, 76 clinical dental, 34 preclinical, and 34 clinical oral and dental health program students. Clinical dental students had significantly higher HU-DBI scores (7.25 ± 1.63) than preclinical dental students (6 ± 1.57). No significant difference was found between preclinical (6.38 ± 1.41) and clinical oral and dental health program students (6.62 ± 2.09). Female students had higher HU-DBI scores (p<0.05). No significant correlations were found with other sociodemographic factors, such as parental education, alcohol, or cigarette use.Conclusion: Integrating preventive dentistry components into the early-stage curriculum may facilitate an earlier enhancement of fundamental knowledge and awareness among future dental professionals, irrespective of sociodemographic factors.